HUBUNGAN BUDAYA DAN LINGKUNGAN PADA SITUS-SITUS GUA PRASEJARAH DI JAWA TIMUR - Jati, Slamet Sujud Purnawan (Jurnal Sejarah dan Budaya, 2010)
Abstract: This research wants to try on explaining distribution of prehistoric cave sites in East Java and studies about relation between sites and environment as resource. Thus, this research does not study one site in detail, but it covers all prehistoric cave sites which be found in East Java areas. Trough this study, it will be tried to learn relationship between one site with another site with environment, and interpret how the past human made decision to choose location as settlement place and human activities life.